THE ANALYSIS OF THE BULLYING IN THE POEMS “I GOT FLOWERS” BY PAULETTE KELLY AND “INCIDENT” BY COUNTEE CULLEN - istiwarni diah (STIBA IEC JAKARTA, 2017)
The purpose of this thesis is to analyze about the kind of bullying that is reflected in the poems “I Got Flowers” and “Incident” and how the bullying occurs in each poem. The analysis uses qualitative and content analysis method. The data are taken from books. The results of the analysis are (1) There are five types of bullying; physical bullying, verbal bullying, emotional bullying, sexual bullying, cyber bullying which are common happen in society. (2) The speakers of the poems get bullying in the different ways. The speaker of poem “I Got Flowers”, who is a woman, suffers verbal, physical, and emotional bullying from her husband but the speaker of poem “Incident”, who is still a little child suffers verbal bullying due to discrimination of race. (3) The speakers of the poems also feel the effects after suffering the bullying. The speaker of “I Got Flowers” is beat to the death because of get the bullying action repeatedly but the speaker of “Incident” has trauma for eight months in Baltimore